(untitled) (Journal of Industrial and Mechanical Engineering, 2019)
Nowadays, cities consume 75% of the energy demanded and function as a refuge for 80% of the population, which leads to exerting high pressure on the environment. Therefore, this research attempts to promote sustainable energies, and thus bring urbanization closer to objective l7 of the SDGs (Sustainable Development Goals) Affordable and Non-Pollutant Energy. For this, it is important to have solar radiation data on several scales. This work presents a survey of tools, study cases and methods available to estimate the solar potential (case study: Autonomous City of Buenos Aires). Finally, the techniques used to select the most appropriate tool for the case study are compared.